PERANCANGAN DAN PEMBUATAN APLIKASI VIDEO STREAMING BAHASA ISYARAT “BETA” BERBASIS ANDROID (STUDI KASUS: “KARANG TARUNA TUNAS SARI KELURAHAN BABAKAN SARI KIARACONDONG”) - Faisyal Rizki Muharam; Amras Mauluddin (SOSIOHUMANITAS, 2020)
On environment karang taruna , the or common people still lacking knowledge or have not been able to speak these cues to communicate or at least say a two broken said with the people the deaf at the time of the event affection for the people with disability especially .It is expected that the application it may help give a forum to learn sign language without considering time and place , and application was built with the methods extreme programming with the methods this is the development of this application made with stage planning , design , coding , testing .With the the application does not have to worry about when time to learn where and with whom , therefore with the this program will ease members of karang taruna especially to learn sign language.